Giant cardiac hydatid cyst: case presentation with radiologic survey and review of literature - Kumar, Ravinder; Kumar, Amit; Argahari, Neha Singh; Jaiswal, Gagan; Kundu, Jyoti (Journal of Kathmandu Medical College, 2015)
Hydatid disease is mostly localised to liver and lungs. Cardiac involvement is a rare but potentially very serious complication of echinococcosis, constituting only 0.5–2% of all cases of hydatidosis. Cardiac hydatid cyst is a diagnostic and therapeutic challenge on account of highly variable clinical presentations and non-specifi c symptoms and often numerous unpredictable complications. We present a case report of 20-year-old man who was admitted to our hospital with chief complaint of palpitations and shortness of breath. Using baseline investigations like ECG, transthoracic echocardiography, ultrasonography, non-contrast computed tomography and magnetic resonance imaging, a giant multiloculated cystic lesion (58.4 mm × 43.3 mm) was diagnosed in the apex of left ventricle. Serologic tests (hydatid cyst antibody) confi rmed Echinococcus infection. Thoracic computed tomography with intravenous contrast was not performed because patient reported history of allergy to contrast. This case report is unusual as it is concerned with the description of a rare disease entity (large cardiac hydatid cyst). Its radiological appearances are discussed for early diagnosis and better understanding of the disease, together with a review of the literature. Journal of Kathmandu Medical College Vol. 3, No. 4, Oct.-Dec., 2014 Page: